Antibiotic utilisation in primary and revision total hip replacement patients: A registry linkage cohort study of 106 253 patients using the Australian Orthopaedic Association National Joint Replacement Registry. Issue 2 (7th September 2022) - de Steiger, Richard N.; Pratt, Nicole L.; Gulyani, Aarti; Duszynski, Katherine M.; Inacio, Maria C.; Graves, Stephen E.; Smith, Paul N.; ,
Abstract: Purpose: Infection is a major complication following joint replacement (JR) surgery. However, little data exist regarding antibiotic utilisation following primary JR and how use changes with subsequent revision surgery. This study aimed to examine variation in antibiotic utilisation rates before and after hip replacement surgery in those revised for infection, revised for other reasons and those without revision. Methods: This retrospective cohort analysis used linked data from the Australian Orthopaedic Association National Joint Replacement Registry and Australian Government Pharmaceutical Benefits Scheme. Patients were included if undergoing total hip replacement (THR) for osteoarthritis in private hospitals between 2002 and 2017. Three groups were examined: primary THR with no subsequent revision ( n = 102 577), primary THR with a subsequent revision for reasons other than periprosthetic joint infection (PJI) ( n = 3156) and primary THR with a subsequent revision for PJI ( n = 520). Monthly antibiotic utilisation rates and prevalence rate ratios (PRRs) with 95% confidence intervals (CIs) were calculated in the 2 years pre‐ and post‐THR. Results: Prior to primary THR antibiotic utilisation was 9%–10%. After primary THR, antibiotic utilisation rates were higher among patients revised for PJI (PRR 1.69, 95% CI 1.60–1.79) compared to non‐revised patients, while the utilisation rate was lower in patients revised for reasons other than infection (PRR 0.96, 95% CI 0.93–0.98). For those revised for infection, antibiotic utilisation post‐revision surgery was two times higher than those revised for other reasons (PRR 2.16, 95% CI 2.08–2.23). Utilisation of injectable antibiotics including, vancomycin, flucloxacillin and cephazolin was higher in those revised for PJI patients 0–2 weeks following surgery but not in those revised for other reasons compared to the non‐revised group. Conclusions: Ongoing antibiotic utilisation after primary surgery may be an early signal of problems with the THR and should be a prompt for primary care physicians to refer patients to specialists for further appropriate investigations and management.